Somatic Approaches to Anatomical Education - He, Marie-Hélène (Université d'Ottawa / University of Ottawa, 2025)
Anatomical sciences in health professions education (HPE) often reduce the human body to a static object of mental contemplation. This disembodied approach isolates anatomical concepts from lived, somatic experiences, neglecting the dynamic interplay between theoretical learning, experiential practice, and sensory embodiment. Such disconnection undermines health professional students' ability to develop the somatic sensitivity and kinaesthetic awareness essential for patient-centred care. This dissertation explores how anatomy educators across diverse disciplines integrate experiential somatic learning methods, which emphasize sensory-based exploration and awareness of the body. These methods aim to bridge the gap between theoretical anatomical knowledge and somatic understanding. In doing so, they also promote perceived intercorporeal connections, or shared bodily experience, in classroom settings. Drawing on multiple case study research methodology and cross-disciplinary comparative analysis, the study traces evolving practices in anatomical education across expressive (visual arts, dance), clinical (medicine, kinesiology), and technical (bioengineering) fields. Guided by the Function2Flow (F2F) framework, this research examines how sensory and affective dimensions of the body are mobilized in educational practice. Findings reveal that educators intentionally integrate movement, gesture, touch, and lived anatomical experiences to cultivate somatic awareness, deepen anatomical exploration through intercorporeal learning, and inspire joy and curiosity in both teaching and learning. This work contributes to the growing discourse on cross-disciplinary somatic pedagogy in anatomical sciences, offering actionable insights for anatomy educators. It advocates for a more experiential, humanized, and integrative approach to anatomy education, particularly one that honours the interconnectedness of mind, body, and environment, and reflects the lived complexity of being human.
Keywords: Somatic learning; anatomy education; interdisciplinary pedagogy; cross-disciplinary pedagogy; living anatomy